Prostaglandin E2 receptor EP4 activation induces tolerogenic dendritic cells to mitigate ischemic acute kidney injury - Chunyao Li; Caiping Yang; Pingping Wang; Aijie Wu; Jiaojiao Zhu; Wenlu Shi; Ying Zhang; Qin Ma; Tao Peng; Jie Xu; Ting Zhang (Scientific Reports)
Abstract The prevalence and mortality rates of acute kidney injury (AKI) remain high, with ischemia-reperfusion (I/R) being a major cause in clinical settings. Dendritic cells (DCs) play a crucial role in inducing the infiltration of inflammatory cells into the kidneys during I/R, leading to persistent kidney damage. However, immature DCs (imDCs) maintain self-tolerance under homeostatic conditions. Therefore, targeting the immunomodulatory duality of DCs to prevent I/R-AKI is of significant importance. In this study, we found Pre-treatment of bone marrow-derived dendritic cells (BMDCs) with the EP4 receptor agonist L-902,688 induced the generation of EP4highCCR7high DC (LDC), However, there was a decrease in its maturation markers (CD80, CD86, and MHCII). Additionally, treatment with the EP4 receptor antagonist GW 627,368 resulted in reduced CCR7 expression on DCs without significantly affecting DC maturation. Furthermore, levels of pro-inflammatory cytokines decreased in the supernatant of LDCs while secretion of the anti-inflammatory cytokine IL-10 surged, indicating that LDCs possess stronger immune tolerance. Subsequent co-culturing mouse renal tubular epithelial cells TCMK-1 with LDCs did not impair TCMK-1 cells viability but rather enhanced cell migration rates. Following hypoxia-reoxygenation (H/R) treatment, TCMK-1 cells co-cultured with LDCs exhibited reduced intracellular ROS levels, improved oxidative stress response, reduced apoptosis, and preserved migratory capacity. In addition, our in vivo pharmacological intervention experiments manifested that the preemptive activation of the EP4 receptor conferred remarkable renal protection by inhibiting renal DC maturation. Collectively, our findings further investigate the involvement of PGE2-EP4 signaling in the regulation of DC immune function, emphasizing the potential benefits of targeting the PGE2-EP4-DC axis for preventing I/R-AKI.